Drag coefficients of double unequal-diameter flexible cylinders in tandem undergoing vortex/wake-induced vibrations. (15th February 2023) - Zhao, Bing; Zhang, Mengmeng; Fu, Shixiao; Fu, Xuepeng; Ren, Haojie; Xu, Yuwang
Abstract: A reliable load-to-response prediction for flexible risers under drag forces can protect the multiple-riser system from collision and optimize its spatial arrangement. To investigate the drag coefficients for double risers in tandem, a series of experiments for two unequal-diameter flexible cylinders in different initial gap spacings was performed under uniform flows with Reynolds numbers up to 11, 328. Based on the reconstructed mean drag displacement from measured strains, a distributed drag force amplified by vortex-induced vibrations can be identified reversely. Meanwhile, a modified wake model was developed to estimate the mean wake velocity for the downstream cylinder. With this mean wake velocity, the drag coefficients of the downstream cylinder were obtained. The features of drag coefficients and vortex/wake-induced vibrations were found to be closer to the corresponding features of an isolated cylinder. Furthermore, an empirical drag coefficient model for double unequal-diameter cylinders in tandem was proposed, which accounts for the drag amplification effect by vibrations, tandem spacing, upstream-to-downstream cylinder diameter ratio, mean wake velocity, etc. The results show that this empirical drag coefficient model can obtain the prediction results with relatively higher precision. Highlights: A series of tests were performed to study the drag coefficients of double unequal-diameter flexible cylinders in tandem. A modified wake model was proposed to predict the wake velocity, considering the VIV of the upstream cylinder. A new drag coefficient prediction model for double unequal-diameter flexible cylinders in tandem was proposed.